Investments - Bodie, Zvi; Kane, Alex, 1942-; Marcus, Alan J. (New York, NY McGraw-Hill Education, 2021)
"Investments, Twelfth Edition, is intended primarily as a textbook for courses in investment analysis. Our guiding principle has been to present the material in a framework that is organized by a central core of consistent fundamental principles. We attempt to strip away unnecessary mathematical and technical detail, and we have concentrated on providing the intuition that may guide students and practitioners as they confront new ideas and challenges in their professional lives."--Provided by publisher.
The investment environment -- Asset classes and financial instruments -- How securities are traded -- Mutual funds and other investment companies -- Risk, return, and the historical record -- Capital allocation to risky assets -- Efficient diversification -- Index models -- The capital asset pricing model -- Arbitrage pricing theory and multifactor models of risk and return -- The efficient market hypothesis -- Behavioral finance and technical analysis -- Empirical evidence on security returns -- Bond prices and yields -- The term structure of interest rates -- Managing bond portfolios -- Macroeconomic and industry analysis -- Equity valuation models -- Financial statement analysis -- Options markets: introduction -- Option valuation -- Future markets -- Futures, swaps, and risk management -- Portfolio performance evaluation -- International diversification -- Hedge funds -- The theory of active portfolio management -- Investment policy and the framework of the CFA Institute.
International student edition.
Includes bibliographical references and indexes.
Keywords: Investments; Portfolio management